Addressing Endogeneity in International Marketing Applications of Partial Least Squares Structural Equation Modeling. Issue 3 (September 2018) - Hult, G. Tomas M.; Hair, Joseph F.; Proksch, Dorian; Sarstedt, Marko; Pinkwart, Andreas; Ringle, Christian M.
Partial least squares structural equation modeling (PLS-SEM) has become a key method in international marketing research. Users of PLS-SEM have, however, largely overlooked the issue of endogeneity, which has become an integral component of regression analysis applications. This lack of attention is surprising because the PLS-SEM method is grounded in regression analysis, for which numerous approaches for handling endogeneity have been proposed. To identify and treat endogeneity, and create awareness of how to deal with this issue, this study introduces a systematic procedure that translates control variables, instrumental variables, and Gaussian copulas into a PLS-SEM framework. We illustrate the procedure's efficacy by means of empirical data and offer recommendations to guide international marketing researchers on how to effectively address endogeneity concerns in their PLS-SEM analyses.